Intermediate Filaments as Organizers of Cellular Space: How They Affect Mitochondrial Structure and Function - Nicole Schwarz; Rudolf E. Leube (Cells, 2016)
Intermediate filaments together with actin filaments and microtubules form the cytoskeleton, which is a complex and highly dynamic 3D network. Intermediate filaments are the major mechanical stress protectors but also affect cell growth, differentiation, signal transduction, and migration. Using intermediate filament-mitochondrial crosstalk as a prominent example, this review emphasizes the importance of intermediate filaments as crucial organizers of cytoplasmic space to support these functions. We summarize observations in different mammalian cell types which demonstrate how intermediate filaments influence mitochondrial morphology, subcellular localization, and function through direct and indirect interactions and how perturbations of these interactions may lead to human diseases.